Gender and the Economic Crisis in Europe
XVII, 282 p. 3 illus. in color.
Keywords: This book is a unique exploration into the gendered politics of the economic crisis in Europe. It focuses, firstly, on the changes in the political and economic decision-making institutions and processes of the EU and their consequences for gender equality policy. Secondly, the book analyses the gendered impacts of austerity politics on member states’ gender equality policies, institutions, regimes, and debates. Finally, it addresses feminist and intersectional struggles and resistances against neoliberal, conservative and racist politics across Europe. The authors consider the gendered politics of the economic crisis from a variety of feminist approaches, shedding new light on the concept of the crisis and on questions of politics, institutions and intersectionality. The case studies included refer to different parts of Europe, from North to South and from East to West, capturing the multifaceted gendered impacts of the crisis. The volume will be of interest to students and scholars of politics, international relations, gender studies, economics, law, sociology, social policy, and European studies. .